Beyond Screen Time: Content-Based Parental Decision Making in Early Childhood Digital Engagement- a Qualitative Study in Indonesia - Saharudin Saharudin; Regita Riani Putri (Sakura Digital Nusantara, 2026)
Purpose: Research on children’s digital media use has traditionally focused on screen time duration, overlooking the importance of content quality and parental decision-making. This study examines how parents make content-based decisions regarding children’s digital media use, moving beyond traditional screen time perspectives. Methods: Using a qualitative approach, data were collected through semi-structured interviews with six parents of early childhood children aged 2-6 years in a private kindergarten in Jambi and analyzed using thematic analysis. Findings: The findings reveal two main themes: content selection by parents and educational purposes of access. Parents actively curate children’s digital environments by selecting age-appropriate, safe, and educational content, rather than focusing solely on limiting screen time. In addition, digital media are increasingly utilized as learning tools to support literacy, language development, and school-related learning. These findings indicate a shift in parental mediation practices toward a more intentional and content-oriented approach to digital parenting. Research Implications: The study contributes to the growing discourse on “beyond screen time” by emphasizing that the quality and purpose of digital media use are more significant than duration alone. It also highlights the critical role of parents as active facilitators of children’s digital engagement. Originality: This study contributes by proposing a process-oriented understanding of content-based parental decision-making, highlighting how parents evaluate, filter, and guide children’s digital media use beyond simple time regulation. The findings suggest that digital parenting is increasingly shaped by content quality and educational intent, emphasizing the role of parents as active facilitators in children’s digital engagement.